Genetic variability of swamp eel Monopterus albus in east coast of Peninsular Malaysia inferred from mitochondrial DNA analysis. - Aliyu Garba, Khaleel; Ahmad Syazni, Kamarudin; Norshida, Ismail; Chew, H.H.; Ing, N.S. (2016)
Swamp eel Monopterus is a highly commercial food fish with medicinal value in Malaysia, where the East Coast Peninsular Malaysia (ECPM) is the second largest contributor of swamp eel' s annual production. Wild stocks reduction due to overfishing has encouraged the breeding and culturing of this species. A better understanding of its genetic variability will aid the breeders to determine how to exploit these natural gene resources effectively. Sixty one samples were collected at six different sampling sites from Kelantan, Terengganu and Pahang to investigate the baseline data on the population genetics structure of the swamp eel in ECPM. The partial mtDNA 16Sr RNA gene detected four haplotypes among all the samples. Haplotype-1 was the most widespread haplotype among the six sampling sites. comprising of 75.4% of all san1ples. Both non-significant values of Tajima's D and Fu 's Fs sugges1ed !hat all populations were at genetic equilibrium . The three distinct haplotypes could be used as a DNA markers or indicators to identify the native population at their respective sampling sites.